Dexamethasone blocks the migration of the human neuroblastoma cell line SK-N-SH - Casulari,L.A. (2006)
Glucocorticoids (Gc) influence the differentiation of neural crest-derived cells such as those composing sympathoadrenal tumors like pheochromocytomas, as well as neuroblastomas and gangliomas. In order to obtain further information on the effects of Gc on cells evolving from the neural crest, we have used the human neuroblastoma cell line SK-N-SH to analyze: 1) the presence and the binding characteristics of Gc receptors in these cells, 2) the effect of dexamethasone (Dex) on the migration of SK-N-SH cells, and 3) the effect of Dex on the organization of the cytoskeleton of SK-N-SH cells. We show that: 1) receptors that bind [³H]-Dex with high affinity and high capacity (Kd of 9.6 nM, Bmax of 47 fmol/mg cytosolic protein, corresponding to 28,303 sites/cell) are present in cytosolic preparations of SK-N-SH cells, and 2) treatment with Dex (in the range of 10 nM to 1 µM) has an inhibitory effect (from 100% to 74 and 43%, respectively) on the chemotaxis of SK-N-SH cells elicited by fetal bovine serum. This inhibition is completely reversed by the Gc receptor antagonist RU486 (1 µM), and 3) as demonstrated by fluorescent phalloidin-actin detection, the effect of Dex (100 nM) on SK-N-SH cell migration is accompanied by modifications of the cytoskeleton organization that appear with stress fibers. These modifications did not take place in the presence of 1 µM RU486. The present data demonstrate for the first time that Dex affects the migration of neuroblastoma cells as well as their cytoskeleton organization by interacting with specific receptors. These findings provide new insights on the mechanism(s) of action of Gc on cells originating in the neural crest.